Traceless Photolabile Linker Expedites the Chemical Synthesis of Complex Oligosaccharides by Automated Glycan Assembly - Le Mai Hoang, Kim (J Am Chem Soc, 2019)
[Image: see text] Automated glycan assembly (AGA) aims at accelerating access to synthetic oligosaccharides to meet the demand for defined glycans as tools for molecular glycobiology. The linkers used to connect the growing glycan chain to the solid support play a pivotal role in the synthesis strategy as they determine all chemical conditions used during the synthesis and the form of the glycan obtained at the end of it. Here, we describe a traceless photolabile linker used to prepare carbohydrates with a free reducing end. Modification of the o-nitrobenzyl scaffold of the linker is key to high yields and compatibility with the AGA workflow. The assembly of an asymmetrical biantennary N-glycan from oligosaccharide fragments prepared by AGA and linear as well as branched β-oligoglucans is described to illustrate the power of the method. These substrates will serve as standards and biomarkers to examine the unique specificity of glycosyl hydrolases.